2010
DOI: 10.1002/da.20777
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression: a rationale for studying exercise

Abstract: Background Major Depressive Disorder (MDD) in pregnancy, or antenatal depression poses unique treatment challenges and has serious consequences for mothers, unborn babies, and families when untreated. This review presents current knowledge on exercise during pregnancy, antidepressant effects of exercise, and the rationale for the specific study of exercise for antenatal depression. Method A systematic literature review was performed using English language articles published in Medline, PsycINFO, CINAHL, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 72 publications
2
44
1
Order By: Relevance
“…It is important to obtain a better understanding of the barriers to practicing physical activity, especially those related to mental health 19,20 . Women are more vulnerable to mental health problems during pregnancy due to the intense psychological and biological changes that occur during this period 19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to obtain a better understanding of the barriers to practicing physical activity, especially those related to mental health 19,20 . Women are more vulnerable to mental health problems during pregnancy due to the intense psychological and biological changes that occur during this period 19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods such as exercise that can improve short and long-term mood status are critical to overall health as psychological health and physical health are closely associated [20]. Anxiety and stress can have negative implications for maternal and neonatal health outcomes [21], so any efforts made to reduce stress and anxiety may also elicit improvements in maternal and neonatal health [22]. A previous study by Gaston and Prapavessis (2013) examining depressive mood scores in pregnant women in response to an exercise program reported a reduction in depressive symptoms after a four-week intervention [23].…”
Section: Mean ± Sd Vo 2max (Ml/kg/min)mentioning
confidence: 99%
“…Interestingly enough, the first scientifically based link between physical health and exercise, or lack of it, was only reported as recently as 1953 by Jerry Morris [2,3]. Since then, exercise has been regarded as a universal remedy for psychological and physical wellbeing, from preventing chronic health conditions to promoting weight loss and better sleep as underlined by numerous scientific studies [4][5][6][7][8][9]. Furthermore, Vaamonde et al have observed that physically active subjects have better semen parameters and hormone levels than sedentary subjects [10,11].…”
Section: Introductionmentioning
confidence: 99%